Does parental education help decrease smoke exposure in children with asthma?. Issue 3 (March 2016) - Smith, Cody; Hudson, Jonell; Coulter, Lois
Abstract : Evidence‐Based Answer : Parental education is associated with a reduction in nicotine exposure in high‐risk asthmatic children (SOR: C, RCT using biochemical outcomes). It is unclear if parental education is an effective mode of reducing smoke exposure in all children with asthma (no SOR given, conflicting RCTs).